Literature Review : Pengaruh Limbah Medis Terhadap Kesehatan Lingkungan Pada Negara Berkembang Di Asia Tenggara - I Wayan Nova Suandita (Indonesian Journal of Health Community, 2025)
Environmental health is a global issue with the potential for significant impact on human health. A particular environmental problem that persists, especially in developing countries, is the issue of medical waste. If not properly managed, medical waste can have detrimental effects on the environment. The objective of this literature review is to determine the influence of medical waste on the environment in developing countries using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. Articles were selected based on specific inclusion and exclusion criteria from Google Scholar, PubMed, and ScienceDirect. This literature review specifically limits its focus to publications released within the last five years, namely from 2020 to 2024. This review discusses medical waste in Southeast Asian developing countries, including Indonesia, Malaysia, Laos, Cambodia, and the Philippines, and briefly explores the environmental impacts of this waste. The findings from the analyzed articles indicate that poorly managed medical waste results in severe environmental pollution and disease transmission. The study concludes that medical waste significantly affects environmental health.